Pemodelan Hydro-Pump Storage Bertenaga Gelombang Laut Menggunakan Simulink - rizki pratama putra (Sekolah Tinggi Teknik - PLN, 2020)
Intermittency problem of wave power energy converter becomes a disadvantage when integrated into a power system, same with another renewable energy plant. In this paper, a method is proposed to solve the intermittency problem of wave energy converter when integrated into a small power system or in standalone mode. The main idea is to integrate a small pumped hydro system to the wave energy converter which the mechanical energy from wave converted to fluid potential energy. This study aims to create mathematical models of the interaction between a wave-powered pump, the reservoir, and the generator. The models then simulated to see how wave amplitude and reservoir height affect the energy output of the plant. From the simulation results, when the amplitude of the wave is varied between 0.6-1.4 m, the highest power output comes with 1 m wave amplitude. The water output debit which has a relation with stored energy also gives its high rate when the wave amplitude is 1 m. The nonlinear relationship between related parameters is nonlinear that optimization technique will be needed to optimize the plant at a specific working condition